EXPLORING THE LEARNING EXPERIENCE OF POSTGRADUATE MEDICAL RESIDENTS IN BEDSIDE CLINICAL SKILLS: A QUALITATIVE ANALYSIS. - Gilani, Syed Yasir Hussain; Bibi, Saima; Junaid, Ayesha; Khan, Junaid Sarfaraz (Journal of Ayub Medical College Abbottabad, 2025)
Background: Sir William Osler, a renowned physician, once said, “Medicine is learned by the bedside and not in the classroom. Let not your conceptions of disease come from the words heard in the lecture room or read from the book. See and then reason and compare and control. But see first”. Objective was to explore the learning experience of Postgraduate Medical Residents in Bedside Clinical Skills and identify the hurdles in good learning experience. Methods: This study was conducted in the Department of Medicine, medical teaching institute of Khyber Pakhtunkhwa in March 2025. The duration was till the saturation of data. The participants were inducted after taking informed consent and proper explanation of the objectives of the study. Induction was through purposive sampling for a focus group comprised of eight postgraduate medical residents from different years of residency. The data analysis was from the audio recordings of the focus group and were transcribed verbatim. From the transcribed data codes were identified to look for themes, sub-themes and individual quotes with in the data. Results: A focus group of eight postgraduate medical students, four male and four female along with a male PGR was part of the study. PGRs were from different years of training and were from the medical department. All participants appreciated the effectiveness of bedside clinical skill teaching. They unanimously agreed on the beneficial role of the supervisor in improving the learning experience. Our participants identified different barriers and suggested ways to overcome them. Overcrowded, hectic, and underequipped medical units are clear barriers to learning, and hospital administration has been identified as a mechanism for addressing this issue. Our participants were unsure regarding the impact of CPSP and PGMI in improving the overall learning experience for bedside clinical skills. Conclusion: Bedside clinical skills teaching by their supervisors as an effective tool to enhance their learning as well as decision making while interacting with the patients. Barriers of fear, overcrowding and poor medical resources are well accepted but with time they eased out by adaptation with the environment